2018
DOI: 10.1038/d41586-018-07695-1
|View full text |Cite
|
Sign up to set email alerts
|

Citations strength begins at home

Abstract: C hina's president, Xi Jinping, wants the country to be a world-class innovator by 2050. To achieve this, there are major challenges for the country to overcome-significantly, the quality of its research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…For the first question, results show similar findings as previous studies (Larivière et al, ; Tang et al, ): most citations of Chinese and US papers are from domestic or partner countries, and shares of Domestic citations of China and the US reach over 60% and 30%, respectively. Compared with Domestic citations , Partner citations (in IC) and Other citations are less in Chinese publications but obviously higher in US publications; this is consistent with relatively higher and lower shares of foreign citations of US and China as reported by National Science Board (, Chapter 5).…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For the first question, results show similar findings as previous studies (Larivière et al, ; Tang et al, ): most citations of Chinese and US papers are from domestic or partner countries, and shares of Domestic citations of China and the US reach over 60% and 30%, respectively. Compared with Domestic citations , Partner citations (in IC) and Other citations are less in Chinese publications but obviously higher in US publications; this is consistent with relatively higher and lower shares of foreign citations of US and China as reported by National Science Board (, Chapter 5).…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…From the cited side (cited references), Mervis () found that Asian scientists were increasingly citing Asian papers, and in the reference lists of Asian papers, the visibility of Asian references was about to equal that of EU and US references. During the period of 1980–1996, about 40% of the references and citations of European papers were other European outputs, and for US, the percentage of US references in the references of US papers were even higher (about 60%) (Larivière, Gong, & Sugimoto, ). From the citing side (citing articles), high percentage of citations from the same country (namely rate of country self‐citation) can be observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of scholarly impact, Larivière et al (2018) examined the percentile rank of selected countries' self‐citations from 2009 to 2017. They found that all countries are more likely to cite other papers from the same country, yet publications from the United States are cited by researchers from all countries.…”
Section: Related Workmentioning
confidence: 99%
“…Slovenia, Spain, Sweden, and United Kingdom) published the paper. These binary variables focus on possible national biases in citations (seeBornmann, Stefaner, de Moya Anegon, & Mutz, 2014;Bornmann, Wagner, & Leydesdorff, 2018;Lariviere, Gong, & Sugimoto, 2018).…”
mentioning
confidence: 99%